A fast measurement of Warburg-like impedance spectra with Morlet wavelet transform for electrochemical energy devices. (1st November 2019) - Li, Weiheng; Huang, Qiu-An; Yang, Changping; Chen, Jian; Tang, Zhepeng; Zhang, Fangzhou; Li, Aijun; Zhang, Lei; Zhang, Jiujun
Abstract: Fast impedance measurement via complex Morlet wavelet transform (CMWT) offers a valuable way for real-time diagnosis and in-situ monitoring on electrochemical energy devices. However, it normally suffers from a dilemma: how to set CMWT parameters such as sampling duration T p, sampling frequency f s, scale factor range A, central frequency f c, and band factor f b ? Especially for a fast measurement of Warburg-like impedance spectra. Thus, optimal theories are needed in order to acquire Warburg-like impedance spectra rapidly under a required precision and a given frequency range. In this paper, the optimal rules for a fast impedance measurement are developed based on the uncertainty principle: 1) 2.5/fL  ≤  T p  ≤ 3.0/fL ; 2) f s  ≥  20fU ; 3) 1.0/ f c ≤ f b ≤1.4/ f c where fL and fU are the lower-limit and upper-limit frequencies of the impedance spectra, respectively. Subsequently, measurement errors are quantitatively evaluated for the reconstructed impedance spectra via CMWT algorithm. Through the derived optimal rules, a fast measurement with T p  =  28.0 s and f s  =  20.0 kHz is implemented for Warburg-like impedance spectra from 0.1 Hz to 1.0 kHz and with the average errors of 0.7% and 2.6% for magnitude and phase, respectively. The developed method creates a higher possibility for real-time diagnosis and in-situ monitoring of electrochemical energy devices in electric vehicles (EVs). Graphical abstract: Image 1 Highlights: Developed the optimal rules for CMWT to reconstruct Warburg-like impedance rapidly. Implemented a fast measurement of Warburg-like impedance based on the optimal rules. Offered a valuable way for the real-time diagnosis on electrochemical energy devices.